2021
DOI: 10.3389/fgene.2021.667877
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Methylation Alterations to Discover Potential Causal Genes Associated With the Survival Risk of Cervical Cancer in TCGA Through a Two-Stage Inference Approach

Abstract: BackgroundMultiple genes were previously identified to be associated with cervical cancer; however, the genetic architecture of cervical cancer remains unknown and many potential causal genes are yet to be discovered.MethodsTo explore potential causal genes related to cervical cancer, a two-stage causal inference approach was proposed within the framework of Mendelian randomization, where the gene expression was treated as exposure, with methylations located within the promoter regions of genes serving as inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…The distance of 500 bps is to some extent arbitrary and experience-based. In fact, the optimal extension distance upstream of TSS is not clear and various choices were applied in prior literature [139]. To examine the robustness of various extension distances, we performed a sensitivity analysis by incorporating methylation CpG sites within distinct extended regions, and found that the extension of the distance upstream of TSS in defining methylation loci seems to be very robust and has little influence on our final identification of mediating genes for methylation levels measured with the 450K platform (S9 Fig).…”
Section: Application To Ten Tcga Cancer Datasetsmentioning
confidence: 99%
“…The distance of 500 bps is to some extent arbitrary and experience-based. In fact, the optimal extension distance upstream of TSS is not clear and various choices were applied in prior literature [139]. To examine the robustness of various extension distances, we performed a sensitivity analysis by incorporating methylation CpG sites within distinct extended regions, and found that the extension of the distance upstream of TSS in defining methylation loci seems to be very robust and has little influence on our final identification of mediating genes for methylation levels measured with the 450K platform (S9 Fig).…”
Section: Application To Ten Tcga Cancer Datasetsmentioning
confidence: 99%
“…15 Recent studies have found that ZNF330 is associated with the survival risk of cervical cancer. 19 However, the function of ZNF330 in B. tabaci still needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…When apoptosis is initiated, it is released to the cytosol and contributes to the release of cytochrome C. It is a mediator of the mitochondrial apoptotic pathway 15 . Recent studies have found that ZNF330 is associated with the survival risk of cervical cancer 19 . However, the function of ZNF330 in B. tabaci still needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we took the TCGA dataset as a case study and conducted a comprehensive investigation of the effects of race imbalance on the statistical and machine learning analytical strategies and discoveries of the project. We quantitatively evaluated how the racial bias could affect the biological outcomes by conducting racial-biased tests in two respective machine learning tasks, i.e., the causal gene discoveries [32] and patient survivorship predictions [33]. In the causal gene discoveries, we found causal genes identified from overall populations were significantly different from those on minor race samples only, even using the race identity as a confounding adjustment.…”
Section: Introductionmentioning
confidence: 99%